2022
DOI: 10.3390/su14137592
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Land Use and Land Cover Changes through the Lens of SDGs in Semarang, Indonesia

Abstract: Land Use and Land Cover Changes (LULCC) are occurring rapidly around the globe, particularly in developing island nations. We use the lens of the United Nations’ Sustainable Development Goals (SDG) to determine potential policies to address LULCC due to increasing population, suburbia, and rubber plantations in Semarang, Indonesia between 2006 and 2015. Using remote sensing, overlay analysis, optimized hot spot analysis, expert validation, and Continuous Change Detection and Classification, we found that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Furthermore, the socio-economic activities developed have an impact on changes in land cover and changes in the characteristics of the urban environment. It is necessary to control and restore environmental quality in relation to the activities developed (Kelly-Fair et al, 2022). Furthermore, changes in the environmental characteristics of the new city area are marked by the use of water catchment areas, land reclamation, and a decrease in the carrying capacity of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the socio-economic activities developed have an impact on changes in land cover and changes in the characteristics of the urban environment. It is necessary to control and restore environmental quality in relation to the activities developed (Kelly-Fair et al, 2022). Furthermore, changes in the environmental characteristics of the new city area are marked by the use of water catchment areas, land reclamation, and a decrease in the carrying capacity of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Reformation era took place and Regional Autonomous Law established in the Mid-1980s in Indonesia, there were eleven new provinces established until 2022 making a total 37 provinces (1), and a total of 514 Districts/Municipalities (2). The establishment of new provinces and districts/municipalities have brought wide consequences to the infrastructures development, changes in land use/land covers and property rights (3), expansion of urban landscapes and transition in farming (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Firman (3) estimated that during 1991 -1993 there was around 106,000 ha agricultural land converted for urban land and mostly for residential areas. The studied of Mulyani et al (4) showed that with the present conversion rate of 96,512 ha/year during 2000 -2015, they predicted that the current of 8.1 million ha of paddy field will be decreased to 5.1 million ha in 2045 if there is no government intervention to slowdown or control it. This will have serious impact on rice self-sufficient program.…”
Section: Introductionmentioning
confidence: 99%
“…Semarang City is the area with the fastest development in Central Java Province. Besides being the provincial capital, the strategic location of the area with PANTURA Road makes the region to experience very rapid progress in development (Arsandi et al, 2017;Pigawati et al, 2019;Kelly-Fair et al, 2022). This can be seen in the increasing density of built-up land, specifically in the lower part ABSTRACT Semarang City has the fastest development in Central Java Province, where the activities are no longer centralized but have expanded to the upper part of the region.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of residents who began to access the upper Semarang area impacted land use changes in the region, specifically the Gunungpati Sub-District area (Juhadi et al, 2021;Kelly-Fair et al, 2022). The existence of the Unnes campus located in Sekaran Village makes the area have infrastructure, including public facilities and trade and service buildings.…”
Section: Introductionmentioning
confidence: 99%